STRENGTHENING COASTAL RESILIENCE THROUGH TIDAL FLOOD MANAGEMENT POLICIES: EVIDENCE FROM TANJUNGPINANG CITY, INDONESIA - S. Berryza Amanda Berryza; Rudi Subiyakto; Okparizan Okparizan (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
Tidal flooding is one of the most frequent hydrometeorological disasters affecting coastal areas in Tanjungpinang City, Riau Islands Province. This study aims to analyze the implementation of hydrometeorological disaster management policies related to tidal flooding and identify factors influencing their effectiveness. A qualitative descriptive approach was employed, with data collected through interviews, observations, and documentation. The analysis was based on the policy implementation model of Van Meter and Van Horn, which includes policy standards and objectives, resources, communication, implementing agency characteristics, implementers’ disposition, and socio-economic conditions. The findings reveal that the Regional Disaster Management Agency (BPBD) has implemented mitigation, preparedness, emergency response, and recovery programs to address tidal flooding. However, policy implementation is constrained by limited resources, inadequate infrastructure, coordination challenges, and the vulnerability of coastal communities. Community participation and institutional commitment have supported disaster management efforts, although improvements are still required. The study concludes that effective tidal flood management requires stronger inter-agency coordination, adequate resources, and active community involvement to enhance disaster resilience in coastal areas.